Life cycle cost analysis of structural concrete using seawater, recycled concrete aggregate, and GFRP reinforcement. (30th June 2018) - Younis, Adel; Ebead, Usama; Judd, Simon
Highlights: A LCCA was performed for structural concrete using seawater and recycled aggregates. Glass fiber reinforced polymer displaced black steel as the reinforcement material. The proposed combination achieved a 50% cost saving over a 100-year life cycle. GFRP was more cost effective as reinforcement than black steel and stainless steel. Results are most sensitive to the selected discount rate and construction costs. Abstract: Using seawater and recycled concrete aggregate (RCA) in a concrete mix is potentially advantageous from a sustainability perspective. However, the high chloride levels expected in such a case demands the use of non-corrosive reinforcement in lieu of normal black steel to avoid corrosion problems. Glass fiber reinforced polymer (GFRP) is considered promising as an alternative reinforcement owing to its corrosion resistance and acceptable mechanical properties that minimize maintenance and repairs and extend service life. However, the relatively high initial cost of GFRP bars may mitigate its potential use. To account for these factors, a life cycle cost analysis (LCCA) has been conducted to establish the relative cost savings of structural concrete combining seawater, RCA, and GFRP reinforcement in high-rise buildings compared with a traditional concrete mix and other reinforcement materials, such as black steel and stainless steel. The proposed combination of seawater, RCA, and GFRP in structural concrete was found to achieve cost savings over a 20-year period following initial construction. The life cycle cost (LCC) obtained for the proposed combination was approximately 50% less than that of the conventional counterpart (i.e. concrete with freshwater, natural aggregates, and black steel) based on a 100-year study period. The use of stainless-steel reinforcement to enhance durability was also found to be potentially advantageous but less cost-effective than using GFRP. The LCC of stainless-steel reinforced concrete was estimated to be 15% lower than that of the traditional steel-reinforced counterpart, with a payback period of 50 years. Results were found to be highly sensitive to the assumed discount rate and construction costs. The proposed combination achieved cost savings only with a real discount rate ( r ) of 5.9% or higher. Likewise, using stainless-steel reinforcement was found cost-effective at r ⩽ 1.35 % and nominal construction costs exceeding 85% of the material cost. The differences in concrete mixture cost, however, appeared to have insignificant influence on the ultimate LCCA results compared to those obtained from altering the reinforcement material.